Development of Life Skills in Coping with Stress for Inmates in Narcotics Cases at Sinjai Class IIB Detention Center (A Review of Preaching Strategies) - Mardianti,; Arifuddin Tike,; Kamaluddin Tajibu, (Jurnal Mercusuar, 2023)
This study focuses on life skill development to address stress among narcotics inmates in Class II B Detention Center in Sinjai Regency, by exploring the employed preaching strategies and the supportive and inhibiting factors in life skill development. The research method employed is qualitative, utilizing data collection through observation, interviews, and documentation, with psychological and preaching approaches. The findings indicate that life skill development with preaching strategies has been successful in aspects such as mandatory literacy, talent and interest development, and entrepreneurship mentoring. Inhibiting factors include differences in inmate characters, illiteracy, minimal mentor human resources, and lack of skills training, while supportive factors consist of adequate facilities and infrastructure and positive responses from inmates. The implications of this study highlight the need for collaboration between the government and the detention center in providing skills training for inmates and mentors, as well as the necessity of continuous training for released inmates to prevent reintegration into negative environments. It is hoped that inmates will be more motivated to participate in the provided development programs to enhance their future prospects.